2013
DOI: 10.1166/jbn.2013.1554
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of <I>Trans</I>-Dehydrocrotonin in Liposomes: An Enhancement of the Antitumor Activity

Abstract: The aim of this study was the encapsulation of trans-dehydrocrotonin (t-DCTN) and its inclusion complexes with hydropropyl-beta-cyclodextrin (HP-beta-CD) in liposomes to improve t-DCTN antitumor activity. The in vitro kinetic profiles of t-DCTN-loaded liposomes (LD) and t-DCTN:HP-beta-CD-loaded liposomes (LC) were evaluated using the dialysis technique. The antitumor activity of LD and LC were investigated against Sarcoma 180 in Swiss mice. Histopathological and hematological analyses were carried out. The amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
3
10
0
1
Order By: Relevance
“…Previous attempts to combine cyclodextrin inclusion complexes with liposomes were limited to passive loading of insoluble drugs (65)(66)(67)(68)(69)(70)(71) or active loading of soluble drugs (72). Passive loading often leads to undesirable membrane incorporation, lowering liposome stability, and is much less efficient than active loading.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to combine cyclodextrin inclusion complexes with liposomes were limited to passive loading of insoluble drugs (65)(66)(67)(68)(69)(70)(71) or active loading of soluble drugs (72). Passive loading often leads to undesirable membrane incorporation, lowering liposome stability, and is much less efficient than active loading.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, applying chemical modications to this natural active compound can alter it's biological and chemical properties. Since incorporating drug-cyclodextrin complexes into liposomes were limited to passive loading, 3,8,22 modied cyclodextrins, bearing ionizable groups (Fig. S2 †), may act as a promising carrier to actively load water-insoluble drugs in liposomes core, avoiding the drug chemical modication risk.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cyclodextrin in the aqueous compartment of nanoliposomes would not affect the characteristics of conventional liposomes but prolong drug release compared to conventional liposomes ( Maestrelli et al, 2010 ; Zhang et al, 2015 ). Although a number of studies on DCL systems have been reported ( Dhule et al, 2012 ; Rahman et al, 2012 ; Lapenda et al, 2013 ; Alomrani et al, 2014 ), to date, the therapeutic application of DCL systems as an ocular delivery system remains to be explored.…”
Section: Introductionmentioning
confidence: 99%